DEVELOPMENT OF CORN FLOUR-BASED RICE ANALOG WITH THE ADDITION OF YLANG FLOWER EXTRACT AS A FLAVOR ENHANCEMENT - Putri Khairi Haditama; Khairani Permatasari; Nimas Aura Sukma; Muhammad Alif Rian; Damat (Jurnal Pangan dan Agroindustri, 2022)
Rice is the biggest staple food source in Indonesia, and its consumption has also become a habit in Indonesia. Rice analog of corn flour and ylang flower extract can be developed to reduce this natural rice consumption. Ylang flower extract can increase the antioxidant content and add aroma to rice analog. This research aims to develop alternative food products that have better physicochemical properties and can prevent degenerative diseases. The study was conducted using a Randomized Block Design (RBD) method with one factor, which is the concentration of ylang flower extract consisting of five levels, including 0%, 35%, 40%, 45%, and 50%. The results showed that the addition of ylang flower extract affects the rehydration power, rice analog color, proximate test results, and antioxidant activity. Furthermore, the addition of ylang flower extract also affects the amylose content and organoleptic test. The best formulation of rice analog was obtained from the addition of 35% ylang flower extract.